2017
DOI: 10.1186/s40494-017-0146-1
|View full text |Cite
|
Sign up to set email alerts
|

A high sensitivity, low noise and high spatial resolution multi-band infrared reflectography camera for the study of paintings and works on paper

Abstract: Background: Infrared reflectography (IRR) remains an important method to visualize underdrawing and compositional changes in paintings. Older IRR camera systems are being replaced with near-infrared cameras consisting of room temperature infrared detector arrays made out of indium gallium arsenide (InGaAs) that operate over the spectral range of ~900 to 1700 nm. Two camera types are becoming prevalent. The first is staring array infrared cameras having 0.25-1 Megapixels where the camera or painting is moved to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 13 publications
0
13
0
Order By: Relevance
“…High resolution multispectral infrared reflectography (MS-IRR) [19,20] was done in order to obtain a more complete visualisation of how the dark underlayers were applied. MS-IRR (50 µm/pixel) was done using two camera systems, the first of which consisted of a Si CCD digital camera and filter that set the spectral sensitivity to 900-1100 nm.…”
Section: Underlayers Outlines and Pentimenti Revealed By Multispectrmentioning
confidence: 99%
See 1 more Smart Citation
“…High resolution multispectral infrared reflectography (MS-IRR) [19,20] was done in order to obtain a more complete visualisation of how the dark underlayers were applied. MS-IRR (50 µm/pixel) was done using two camera systems, the first of which consisted of a Si CCD digital camera and filter that set the spectral sensitivity to 900-1100 nm.…”
Section: Underlayers Outlines and Pentimenti Revealed By Multispectrmentioning
confidence: 99%
“…This greatly improves the transparency of pigments such as lead white, which lack any electronic absorption bands in the visible and infrared (400-2500 nm) [3]. While traditionally infrared reflectography is collected in one broad spectral band, recent research has shown that collecting images in narrower spectral bands can help to isolate different phases of the painting process: for instance, to distinguish a preparatory drawing-often applied with an infrared-absorbing material-from the partially penetrated paint layers [20]. These narrower spectral bands (3-300 nm) also allow for specific pigments to be separated from each other within the paint layers [3].…”
Section: Underlayers Outlines and Pentimenti Revealed By Multispectrmentioning
confidence: 99%
“…Conventional IRR is performed by acquiring the image in wide near infrared band, but recently multispectral sensors collecting several narrower NIR bands are becoming increasingly popular [99]. Since the pigment's layer of a painting absorbs much less infrared radiation compared to visible radiation, the presence of underdrawings may be detected as well as changes in the composition [95,100,101]. Near infrared reflectography has proved its usefulness in pigment identification and distinguishing replicas [102].…”
Section: Remote Sensing Techniquesmentioning
confidence: 99%
“…By adding the temporal information to 3D spatial data and database containing descriptive information, it is more and more common to build a temporal GIS (or 4D GIS) allowing one to query and visualize objects belonging to cross-cut different time periods [189]. Depicting archaeological data complexity, 4D GIS has been used in many archaeological applications [100,[190][191][192][193].…”
Section: Archaeologymentioning
confidence: 99%
“…Spectral imaging is an emerging tool in analysis in the field of conservation and restoration of Cultural Heritage (CH) [1,2]. Some of the most relevant applications found are the identification of pigments and materials used in the original artworks [3,4], the characterization of the preservation state using spectral ranges beyond the visible [5] and the visualization of hidden layers or "pentimenti" using the infrared range [6]. However, few studies have focused on the use of spectral imaging on the ageing process of the materials commonly used in artworks or ancient texts [7,8].…”
Section: Introductionmentioning
confidence: 99%